The impact of migration on deaths and hospital admissions from work-related injuries in Australia. - Reid, Alison; Peters, S.; Felipe, N.; Lenguerrand, E.; Harding, S. (2015)
OBJECTIVE: The shift from an industrial to a service-based economy has seen a decline in work-related injuries (WRIs) and mortality. How this relates to migrant workers, who traditionally held high-risk jobs is unknown. This study examined deaths and hospital admissions from WRI, among foreign and Australian-born workers. METHODS: Tabulated population data from the 1991 to 2011 censuses, national deaths 1991-2002 and hospital admission for 2001-10. Direct age standardised mortality and hospital admission rates (DSRs) and rate ratios (RRs) were derived to examine differences in work-related mortality/hospital admissions by gender, country of birth, employment skill level and years of residence in Australia. RESULTS: DSRs and RRs were generally lower or no different between Australian and foreign-born workers. Among men, mortality DSRs were lower for nine of 16 country of birth groups, and hospital admissions DSRs for 14 groups. An exception was New Zealand-born men, with 9% (95%CI 9-13) excess mortality and 24% (95%CI 22-26) excess hospital admissions. CONCLUSIONS: Four decades ago, foreign-born workers were generally at higher risk of WRI than Australian-born. This pattern has reversed. The local-born comprise 75% of the population and a pro-active approach to health and safety regulation could achieve large benefits.